Development of Batu Kumbung Tourism Village Based on Creative Economy - Rahman, Rahman; Ihyana hulfa; Baiq Nikmatul Ulya; Siti Hamdiah Rojabi (Jurnal Internasional Riset Bisnis Pariwisata, 2023)
Batu Kumbung comprises one of the many Tourism Villages located within the Lingsar District of West Lombok Regency. Among the various tourist attractions on offer, visitors can enjoy horticultural tourism, fisheries, cultural experiences, creative arts, handicrafts, ecotourism, and agricultural experiences. These include Tirta Tourism Village, Cultural Tourism Village, Mina Tourism Village, Arts Tourism Village, Agricultural Tourism Village, Ecotourism Village, Craft Tourism Village, and Agro Tourism Village. The objective of this project is to promote a variety of tourism options in each of the village's hamlets, focusing on their unique characteristics. To support the development of a creative economy-based tourism village, a comprehensive study is required. This study employed qualitative methods by collecting data through field observations, interviews, and literature studies. The findings illustrated that the Batu Kumbung tourism village development model features various tourist attractions, including swimming pool tours and processed catfish delicacies such as shredded catfish, catfish skin crackers, and catfish nuggets. These attractions are capable of drawing tourists from distant regions and visitors from NTB. The creative economy of Batu Kumbung tourism village could encompass approximately 90 UMKM players hailing from the village itself, with 60 of these participants actively engaged in the development of Batu Kumbung tourism village.